Large Volume Paracentesis Associated with Intravenous Albumin Management of Patients With Cirrhosis and Ascites - S. KAPICIOĞLU; A. BAKİ; O. YEŞİLDAĞ; N. KAYA; H. KAHRAMAN; M. ESER (Turkish Journal of Gastroenterology, 2020)
-